Isoflavone supplementation reduced serum sex hormone-binding globulin concentration in postmenopausal women - Parwanto, ML. Edy; Indrawati, Yanti; Setiawan, Herman (Faculty of Medicine, Trisakti University, 2012)
IntroductionThe bone loss that occurs with ageng in postmenopausal women is related to a decrease in serum levels of bioavailable estrogen and testosterone, which are mainly bound to sex hormone-binding globulin (SHBG) and albumin. Phytoestrogens are thought to exert hormonal effects in the body due to their structural resemblance to 17Ã¢-estradiol. The objective of this study was to evaluate the effect of isoflavone supplementation on levels of SHBG in postmenopausal women aged 47- 60 years. Methods A study of pre and post test design with controls was conducted in 70 women aged 47- 60 years. Subjects were randomly divided into 2 groups, the isoflavone group received 100 mg isoflavones/day + calcium 500 mg/day and the control group calcium 500 mg/day for 6 months. Measurement of bone mineral density was performed prior to supplementation, and serum SHBG levels before and after supplementation. Results Supplementation of isoflavones for 6 months reduced the SHBG levels by 31.1% in the isoflavone group (p=0.000), whereas supplementation of calcium for 6 months did not affect the levels of SHBG in the control group (p=0.359). Supplementation of isoflavones for 6 months reduced SHBG levels of postmenopausal women in the isoflavone group with either osteopenia (p=0.028) or osteoporosis (p=0.008).Conclusion Supplementation of isoflavones for 6 months decreased the SHBG levels of postmenopausal women in the isoflavone group with osteopenia and osteoporosis. Our findings suggest that phytoestrogens may significantly decreased SHBG levels in postmenopausal women.